Pemanfaatan Limbah Botol Plastik Jenis PET pada Pembuatan Beton Berpori - Nurfitri Anggraeni; Yusrianti Yusrianti; Amrullah Amrullah (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2020)
The waste problem is a big problem all over the world. Every year the use of plastic has increased quite high. This increase is based on changes in living conditions and development of activities. With the accumulation of plastic waste, it will have a bad impact on the environment. To overcome this problem, this research will recycle plastic waste as a mixture of construction materials. This study aims to determine the use of PET plastic bottle waste materials to substitute fine aggregate on the compressive strength and water absorption test. The experimental method is used in research by observing and testing carried out in the laboratory using 12 test objects, using SNI to plan the concrete mixture. The results showed that the compressive strength test value was 0% 24.85 MPa, 3% 8.42 MPa, 6% 4.79 MPa, and 9% 2.56 MPa. And the results of the water absorption test resulted in an average of 0% of 0.39%, 3% produced 2.46%, 6% produced 3.38% and 9% produced 4.10%.